Efeitos de anisotropias em modelos de Ising de spins mistos - Silva, David Cristiano da (2019)
In this work, we have performed Monte Carlo simulations to study the effects of anisotro- pies on two mixed-spins ferromagnetic systems on the square and cubic lattices. These two systems consist of two interpenetrating sublattices, such as: model-I with spin-1/2 (states ±1/2) occupying the sites of sublattice A, while the spin-1 (states ±1 and 0) oc- cupy the sites of sublattice B, and the model-II with spin-1 (states ±1 and 0) occupying the sites of sublattice A, while spin-3/2 (states ±3/2 and ±1/2) occupy the sites of su- blattice B. We calculated the total magnetization mT and the sublattice magnetizations mA and mB, susceptibility chiL, fourth-order Binder cumulants for magnetization UL and energy VL, specific heat Ce, both as a function of temperature T and anisotropy, for both models. In the model-I, we have found the phase diagram in the critical temperature Tc versus anisotropy D plane and shown that this system does not exhibit a tricritical behavior, presenting only second-order phase transition lines between the ordered F and disordered P phases on the square and cubic lattices. For the case of model-II, we have obtained the phase diagram in the critical temperature Tc versus anisotropies DA and DB plane acting on the sublattices A and B, respectively. This model presents first- and second-order phase transition lines between the ordered phases of the type FI , FI I and the disordered phase P, i. e., it presents a tricritical behavior and we also have obtained tricritical point lines. The phase diagram also present second-order phase transition lines between the two different ordered phases FI and FII .